My first farm let's get working! - Sirett, Dawn; Lloyd, Clare; Mewati, Gunjan; Moul, Robin (London dorling kindersley, 2022)
"This busy board book with tabs gets little ones thinking, talking, and learning new words! Come and meet everybody on the farm! What is that chugging noise in the field? Who is hiding in the barn? From tractors and farm vehicles to a farmyard full of animals, babies and toddlers will love learning all about the things you find on the farm
Scientific notions
Keywords: Science